A multimodal approach to eye melanoma: patterns of care and related complications - Maria Grazia Fabrini; Federica Genovesi-Ebert; Franco Perrone; Letizia Forte; Antonella Grandinetti; Stanislao Rizzo; Luca Cionini (Frontiers Media S.A., 2011)
We describe the results of multimodal treatment of uveal and conjunctival melanomas. A retrospective analysis was performed on 54 patients treated with a multimodal approach between 2003 and 2008 in a single institution. Main outcome measures were survival, enucleation rate, local tumor control, visual function preservation and complications associated with treatments. The median follow-up was 33.4 months. The 5-year overall survival was 95.3%, the local recurrence was 3.7% and the 5-year enucleation was 9.4%. Vision preservation was achieved in 84% of cases. Observed complications were cataract, retinal detachment, diplopia, glaucoma, retinopathy, optic neuropathy and scleral necrosis. A careful consideration of treatment of uveal melanoma in this study allowed us to obtain the survival rates and visual outcomes similar to previously published results, with a very small incidence of complications. the results must be interpreted in the light of recent findings on the genetic pattern of uveal melanoma.